(3GdJPgjH aj TQM GdJgPjHs - (3GdNHjUj, aNQ GdOjf, YHjO Gddg Hf aVd Gddg, J (B1050 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Ef CMb eG jJRjf HfTQg efWb GdeGVj hGdMGVQ hjJhTM HPcQg UOhQ GdcJH hGdOaGJQ MeO Gddg Ld LdGdg Ydi GdBjI GdeRgQI GdQjGV hTcQg Ye fhGdg Ydi fYeGFg GdeJQYI GdMjGVs
(3BNQgG (B:s
(3heY Pdc aEfj eYJQa HbdI GdHVGYI hQLd aj eVeGQ Jdc GdUfGYI EP de jJjSQ dj GdGWdGY Ydi GdcJH GdefWbjI EdG Yi TQM GdQSGdI GdTeSjI aGSJNQLJ efgG GdeSGFd Ydi MSH Pgfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/196s
(3cTa GdXfhf (B1/516s
(3gOjI GdYGQajf (B1/650s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs